2018
DOI: 10.5194/acp-18-11647-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotope fractionation during gas-to-particle conversion of NO<sub><i>x</i></sub> to NO<sub>3</sub><sup>−</sup> in the atmosphere – implications for isotope-based NO<sub><i>x</i></sub> source apportionment

Abstract: Abstract. Atmospheric fine-particle (PM2.5) pollution is frequently associated with the formation of particulate nitrate (pNO3−), the end product of the oxidation of NOx gases (NO + NO2) in the upper troposphere. The application of stable nitrogen (N) (and oxygen) isotope analyses of pNO3− to constrain NOx source partitioning in the atmosphere requires knowledge of the isotope fractionation during the reactions leading to nitrate formation. Here we determined the δ15N values of fresh pNO3− (δ15N–pNO3−) in PM2.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“…The MixSIAR allows the user to create a mixing model, based on their data structure and research questions, via options for fixed/random effects, source data types, priors, and error terms (Stock & Semmens, 2017 In the first model, we considered two main pathways (HNO 3 (1) and HNO 3 (2)) in the formation of NO 3 − . The contribution ratio (γ) of HNO 3 (1) can be calculated via the MixSIAR model, as follows (Chang et al, 2018;Zong et al, 2017):…”
Section: /2020jd032604mentioning
confidence: 99%
“…The MixSIAR allows the user to create a mixing model, based on their data structure and research questions, via options for fixed/random effects, source data types, priors, and error terms (Stock & Semmens, 2017 In the first model, we considered two main pathways (HNO 3 (1) and HNO 3 (2)) in the formation of NO 3 − . The contribution ratio (γ) of HNO 3 (1) can be calculated via the MixSIAR model, as follows (Chang et al, 2018;Zong et al, 2017):…”
Section: /2020jd032604mentioning
confidence: 99%
“…Our results suggest that NO 2 influences the organic molecular compositions in urban aerosols. It is noteworthy that the major source of NO 2 is vehicular exhaust (Kendrick et al, 2015); however, coal combustion can also emit NO x into the atmosphere (Chang et al, 2018). Previous studies have also reported that NO x could affect SOA formation (Kanakidou et al, 2005;Mochizuki et al, 2015).…”
Section: Diurnal Variations and Meteorological Conditionsmentioning
confidence: 99%
“…These results indicate that fossil fuel combustion is an important contributor to Nanjing aerosol during winter. Wang and Kawamura (2005) reported that fossil fuel combustion (52 %) was the largest contributor to total organics followed by biomass burning (14 %) and SOA (10 %) from Nanjing, whereas coal combustion was found to contribute 39.5 % to PM 2.1 in Nanjing in 2010 (Chen et al, 2015). Gao et al (2013) pointed out that coal combustion was the dominant (58 %) contributor to PM 2.5 followed by biomass burning (31 %) and vehicular emissions (11 %) in the Pearl River Delta region (two urban, two suburban and two rural sites) for samples collected in 2009.…”
Section: Source Apportionment Of Organic Aerosols Using Pmfmentioning
confidence: 99%
“…They found that HNO 3 formed in the experimental chamber when burning pine has a high δ 15 N value of +11.2‰. Chang et al (2018) observed high δ 15 N-NO 3 − values of +12.2‰…”
Section: Forest Fire-derived Atmospheric Nitrogenmentioning
confidence: 94%